Strengthening actions to increase the participation of women in rural development programs and projects in the southern area: Argentina, Brazil, Chile, Uruguay and Paraguay - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación a la Agricultura (IICA), 2020)
The origin of the proposal is presented together with the specific problem the project seeks to solve, and the justification in finding solutions to the problems of rural women, because of a new perception of their potential contribution to agriculture in Argentina, Brazil, Chile, Uruguay y Paraguay. The specific objetive is to create mechanisms for joint action among the countries of the Southern Area, to be used in identifying and establishing priorities for differentiated policies and instruments which will facilitate the participation of rural women in development. As a final result it hopes to ptovide updated information and basic studies available on the situation of rural women in the Southern Area; senior technical personnel trained in formulating policies and preparing programs promoting the participation of women in rural development; policy and mechanism to ensure on-going funding of projects for rural women.